THEORETICAL FRAMEWORKS OF SOCIAL INTERACTION IN URBAN SPACES: A SYSTEMATIC REVIEW OF SPACE SYNTAX PERSPECTIVES - Audri, Delia Suci; Kusdiwanggo, Susilo; Asikin, Damayanti (Tata Kota dan Daerah, 2025)
This systematic review of 138 peer-reviewed articles published in the past decade, sourced from ScienceDirect, examines the role of spatial connectivity in shaping social life. Employing the PRISMA methodology, 18 high-quality articles were meticulously analyzed using targeted keywords such as “space syntax,” “social interaction,” “connectivity,” and “integration.” The review identifies three key domains that structure social life: spatial accessibility, urban design configuration, and mobility infrastructure. Drawing from urban planning, sociology, and architectural theory, a conceptual model emerges, elucidating how spatial connectivity fosters interaction, well-structured design supports engagement, and integrated mobility enhances social capital. These findings provide actionable insights for planners and policymakers, enabling them to develop post-pandemic resilience and inclusive spatial strategies. However, the limited dataset signals the need for future research that incorporates broader contexts and advanced analytical technologies.